Studium interakce vybraných léčiv s mikroplasty - Ioani, Aldina (Vysoké učení technické v Brně. Fakulta chemická, 2021)
Předložená bakalářská práce se věnuje studiu interakce vybraných léčiv ze skupiny analgetik a antibiotik s mikroplasty. Analýza probíhala ve střední infračervené oblasti, která se využívá k identifikaci chemické struktury látek. Jako metodika byla využita infračervená spektroskopie s Fourierovou transformací. Vzorky byly podrobeny technice zeslabeného úplného odrazu. Jako analyty byly vybrány ibuprofen a trimethoprim z důvodu nadměrného užívání těchto léčiv v populaci. Sorpce léčiv probíhala na polyhydroxybutyrátu, který se řadí mezi biodegradabilní plasty, a polyethylentereftalátu, který je získán synteticky. Z experimentáních hodnot vyplývá, že ke studiu interakce s léčivy, je vhodnější použít biodegradabilní plast PHB, jenž ukázal lepší výsledky. Výběr rozpouštědla je klíčovým faktorem, který má vliv na výsledná spektra.

The bachelor thesis aims to study the interaction of selected pharmaceuticals from the group of analgesics and antibiotics with microplastics. The analysis was conducted in the mid-infrared region, which is used to identify chemical structure of the substances. Fourier transform infrared spectroscopy was used as an analytical method. The samples were subjected to technique attenuated total reflection. Ibuprofen and trimethoprim were chosen as analytes due to their common usage in the population. Sorption of pharmaceuticals was undergoing on polyhydroxybutyrate, which is a kind of biodegradable plastics and polyethene terephthalate, which is synthetic. Measured results showed that for the study of interaction with pharmaceuticals, it is more suitable to use biodegradable plastic polyhydroxybutyrate than polyethene terephthalate because of its better results. Infrared spectra output is very influenced by a selection of a solvent.
Study of the interaction of selected pharmaceuticals with microplastics
Keywords: Infračervená spektroskopie s Fourierovou transformací; zeslabený úplný odraz; polyethylentereftalát; polyhydroxybutyrát; ibuprofen; trimethoprim; Fourier Transform Infrared Spectroscopy; Attenuated Total Reflection; polyethylene terephthalate; polyhydroxybutyrate; ibuprofen; trimethoprim